SUBAK SYSTEM FOR ENVIRONMENTAL DEVELOPMENT BASED ON TRI HITA KARANA - Windia, Wayan; Suamba, I Ketut; Sumiyati, Sumiyati; Tika, Wayan (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol.12, No.1, 2018DO - 10.24843/SOCA.2018.v12.i01.p10, 2018)
Subak in Bali having some wisdom. One of it is an ecological wisdom. The subak ecological wisdom basically based on the Tri Hita Karana (THK) philosophy. UNESCO recognition for subak as a world cultural heritage, because subak directly implemented the THK philosophy in their activities. The components of THK philosophy are parhyangan, pawongan, and palemahan. On parhyangan component, subak is developing harmony on spiritual sector, through some ceremonies at farmer and also at subak level. On pawongan component, subak is developing harmony on social sector, through work together at subak site, and also implementing water borrowing system among subak members in one subak site. Water borrowing system also implemented among subaks that get water from one river. On palemahan component, subak is developing harmony on fisical sector through developing the rice fileds along the land contour, without destroying the land. It’s constructing the beautiful rice field terrace at some subaks in Bali, that it is very famous in the world tourism.